Adolescentes vítimas de traumatismo maxilofacial decorrente de violência interpessoal: uma análise socioespacial - Giovanna Oliveira Souza (2017)
Violence among adolescents in Brazil has increased alarmingly and shows numbers of an epidemic. The maxillofacial injuries intimidate and often disfigure the face of their victims, which in adolescence may generate among many others, psychological trauma and may lead to other future problems. The socio-spatial mapping of the homes of victims of violent acts favors the planning and organization of governmentactions that can be effective in providing security to the population. The present study aims to make an epidemiological and socio-spatial analysis of data referring to interpersonal violence among adolescents 10-19 years in Belo Horizonte, through the marker maxillofacial trauma.This study can corroborate national data and also contribute to the mapping of violence among adolescents in the capital city of thestate of Minas Gerais. Data from this research will be collected from the maxillofacial injuries research database as markers of urban violence in Belo Horizonte-Minas Gerais: an epidemiological and socio-spatial analysis.